Performance of the Budget of the Regional Representative Council of Tanjungpinang City, Riau Island Province - Muhammad Arif; Endang Larasati; Sri Suwitri (International Journal of Science and Society, 2020)
The shift of paradigm in the government system that prioritizes the application of the principles of good governance has also been implemented in Indonesia through Government Regulation No. 68/2010. One of the tasks of the legislature in order to increase the value of government effectiveness is the function of checks and balances. If this function is carried out properly by the legislature, then at least it can increase the effectiveness of the Indonesian government. In relation to budgeting, the budgeting process starts from the discussion of the General APBD Policy (KUA), discussion of the APBD draft submitted by the regional head, to the implementation and accountability of Regional Regulations concerning the APBD. In the context of good governance, the participation of the DPRD must be realized in every process of preparing the APBD by upholding fiduciary duties. The universal principles of good governance are very precisely applied in realizing the budgeting function. In the context of good governance, the participation of the DPRD must be realized in every process of preparing the APBD by upholding fiduciary duties. The universal principles of good governance are very precisely applied in realizing the budgeting function.